Produktivitas Bongkar Muat Angkutan Retail di PT Kereta Api Indonesia - Putri Ryandini, Salsabila; Kholidin, Kholidin (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2024)
PT Kereta Api Indonesia (Persero) Operational Area IV Semarang is one of the state-owned enterprises that operates its business activities in the field of railroad transportation services, which provides facilities and infrastructure to support the smooth transportation of passengers and goods. Along with the increasing flow of goods and loading and unloading operations, all stakeholders involved in the railroad sector are increasingly improving the quality of work and service so that all operations at the terminal run well. This study aims to determine the causes of decreased loading and unloading productivity and the influence of facility factors, human resources, and time on the productivity of loading and unloading retail freight. This research was conducted at PT Kereta Api Indonesia DAOP IV Semarang UPT Terminal Semarang Tawang. Data collection was done through questionnaires, observation, and documentation. This study employs quantitative research methods. The data processing shows that the drop in the productivity of loading and unloading retail transportation is due to a number of things, such as the facilities for loading and unloading (X1), the number of workers (X2), and the amount of time spent loading and unloading (X3). The SPSS output shows that all three of these variables have some effect on the productivity (Y) of retail freight at PT Kereta Api Indonesia DAOP IV UPT Terminal Semarang Tawang.